Antifungal activity of artocarpus altilis leaf extract / Faridah Boiran - Boiran, Faridah (Faculty of Applied Sciences, 2016)
The study was aimed to determine the antifungal activity of Artocarpus altilis leaf extract and to compare the effectiveness of leaf extract in three different types of solvent (ethanol, chloroform and water). Antifungal activity was tested against four pathogenic fungi (Aspergillus fumigatus, Aspergillus niger, Tricophyton sp and Malassezia sp) using disc diffusion method by indicating the presence of the clear zone of inhibition around discs impregnated with different concentration of extract (12.5, 25, 50 and 100 mg/ml). The positive control used was fluconazole and negative control was the solvent itself without extract. The result showed that water extract was the most effective compared to other solvents used (ethanol and chloroform) indicated by the highest inhibitory activity against the tested fungi. The only two fungi were inhibited (Aspergillus fumigatus and Aspergillus niger) at concentration 25, 50 and 100 mg/ml with concentration dependent manner. Aspergillus species were more susceptible as indicated by the largest diameter of inhibition zone at 13.33 mm of diameter against Aspergillus fumigatus followed by Aspergillus niger at 12.67 mm, while Tricophyton sp and Malassezia sp showed resistant to all different concentration of extracts. The result suggested that the Artocarpus altilis leaf extracts have the promising of low therapeutic potential against certain fungi.